Is Topic Fatigue an International Problem? Four Theses (Global Media Journal - German Edition, 2018)
Topic fatigue is a potential reaction to news topics that the media covers intensively. Recipients experiencing topic fatigue are annoyed and state that they do not want to hear or see anything about such topics anymore. As potential outcome, they strive to avoid such topics during their future news exposure. In this essay, we discuss the question of whether topic fatigue is an international problem. Based on initial empirical insights obtained via qualitative interviews, we establish four theses that underline the international meaning of the phenomenon. First, we argue that the level of press freedom can shape the intensity of topic fatigue and that fatigue experiences can be extreme in countries with low press freedom. Second, we discuss topic fatigue as a potential threat to political transitions and democratization processes. Third, we propose that topic fatigue may reinforce resentments against western societies. Regarding this point, the role of the international media in particular for English-speaking, non-western countries is addressed. Finally, we introduce the argument that topic fatigue may erode the deliberative potential of social media, which can be particularly problematic for countries in which the traditional news media is (politically) dependent. Ultimately, the key elements of these theses are used to propose a comparative research design for an international study on topic fatigue.
Keywords: Topic fatigue; news avoidance; news coverage perception; press freedom; international media; hostile media; political alienation; social media; echo chamber